Menemukan Dan Membentuk Cita-Cita Bersama Anak Panti Asuhan Nazar Indonesia - Dhea Oktaviani Rauna Sitompul, Esica; Suriadi, Agus (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Goals are desires, hopes, or goals that a person wants to achieve and thinks about in the future. The usefulness in one's life is that one has something to focus on and work towards, which helps one to be productive, helps one to learn about perseverance in pursuit of goals, builds and increases self-confidence, and helps one to focus and make good decisions because every decision has an impact on the achievement of one's goals. In determining goals, parents have a big role, namely as the child's first image, example, and also the function of parenting. Problems were found by practitioners when orphanage children could not determine their goals. This Field Work Practice uses mezzo intervention methods, namely group work in handling client problems. Intervention is the act of making changes to individuals, groups, and communities that experience impaired functioning. The objectives of the intervention include restoring the client's social functioning, overcoming and preventing problems, achieving community social improvement, encouraging clients to develop the ability to utilize environmental resources. The handling of client problems is carried out together using existing stages, namely engagement, intake, & contract, assessment, planning, intervention, evaluation, and termination. In its application, it is concluded that clients can learn well using the help of image media and can determine their goals.